Nutritional quality of kabuli and desi chickpea in Argentina: effects of environment - Balbo, Raquel; Balzarini, Mónica; Carreras, Julia; Allende, María José; Aguilar, Roxana; Silva, Mercedes Pilar; Karlin, Marcos Sebastián; Alvarez, Carolina; Martinez, Maria Jose (American Society of Agronomy, 2024)
The environment to which a crop is exposed during the growing season has a signif icant impact on seed composition. The objectives of this study were to (1) estimate the contribution of genotype (G), environment (E), and their interaction (G × E) to the agronomic features and seed quality of chickpea and (2) identify climatic variables that significantly affect chickpea nutritional composition. A total of 10 pre commercial and commercial cultivars of Cicer arietinum L. were evaluated in 15 environments in Argentina. Average plant height ranged between 44.7 and 55.2 cm, 100-seed weight was 38 and 27 g, and grain yield was 750 and 1500 kg ha−1 for kab uli and desi chickpea, respectively. The results obtained from the variance component analysis showed statistically significant (p < 0.05) contributions of the effects of G, E, and G × E interaction on the nutritional quality of chickpea seeds. Protein, car bohydrates, and mineral content were mostly affected by E, whereas oil content was G-dependent. Only tocopherols were affected by G × E interaction. The total phe notypic variance is mostly composed of environmental effects captured during the seed filling period. High mean daily air temperature had a negative effect on carbo hydrates and increased protein and mineral content. The fatty acid profile and gamma tocopherol contents were affected by accumulated precipitation and evapotranspira tion. Air humidity was negatively correlated with protein content and iodine value. Results from this research are useful for breeders to broaden the genetic background of chickpea genotypes and for farmers to identify climatic conditions that impact grain quality.